CURRENT VIEW ON ANTICOAGULANT AND THROMBOLYTIC TREATMENT OF ACUTE PULMONARY EMBOLISM - G. A. Ignatenko; G. G. Taradin; N. T. Vatutin; I. V. Kanisheva (Архивъ внутренней медицины)
The presented review concerns contemporary views on specific aspects of anticoagulant and thrombolytic treatment of venous thromboembolism and mostly of acute pulmonary embolism. Modern classifications of patients with acute pulmonary embolism, based on early mortality risk and severity of thromboembolic event, are reproduced. The importance of multidisciplinary approach to the management of patients with pulmonary embolism with the assistance of cardiologist, intensive care specialist, pulmonologist, thoracic and cardiovascular surgeon, aimed at the management of pulmonary embolism at all stages: from clinical suspicion to the selection and performing of any medical intervention, is emphasized. Anticoagulant treatment with the demonstration of results of major trials, devoted to efficacy and safety evaluation of anticoagulants, is highlighted in details. Moreover, characteristics, basic dosage and dosage scheme of direct (new) oral anticoagulants, including apixaban, rivaroxaban, dabigatran, edoxaban and betrixaban are described in the article. In particular, the management of patients with bleeding complications of anticoagulant treatment and its application in cancer patients, who often have venous thromboembolism, is described. Additionally, modern approaches to systemic thrombolysis with intravenous streptokinase, urokinase and tissue plasminogen activators are presented in this review. The indications, contraindications, results of clinical trials devoted to various regimens of thrombolytic therapy, including treatment of pulmonary embolism by lower doses of fibrinolytic agents, are described.